Case report: COPA syndrome with interstitial lung disease, skin involvement, and neuromyelitis spectrum disorder - Li, Xiao; Tang, Yu; Zhang, Lei; Wang, Yuan; Zhang, Weihua; Wang, Ying; Shen, Yuelin; Tang, Xiaolei (Frontiers in Pediatrics, 2023)
This report describes a case of a 22 months Chinese boy with COPA syndrome bearing the c.715G>C (p.A239P) genotype. In addition to interstitial lung diseae, he also suffered from recurrent chilblain-like rashes, which has not been previously reported, and neuromyelitis optica spectrum disorder (NMOSD), which is a very rare phenotype. Clinical manifestations expanded the phenotype of COPA syndrome. Notably, there is no definitive treatment for COPA syndrome. In this report, the patient has achieved short-term clinical improvement with sirolimus.